2010
DOI: 10.1016/j.rmed.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and impact of coronary artery disease in idiopathic pulmonary fibrosis

Abstract: There is a higher prevalence of CAD in IPF patients compared to a similarly matched COPD group. This increased association appeared to be independent of common coronary artery risk factors. IPF patients with significant CAD appear to have worse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 163 publications
(117 citation statements)
references
References 21 publications
11
103
1
2
Order By: Relevance
“…25 A recent study of 73 IPF and 56 COPD patients found the prevalence of coronary artery disease was higher in those with IPF (65.8% vs. 46.1%), with more severe disease also being more common in those with IPF. 5 People with IPF who have severe coronary artery disease also appear to have worse outcomes. 5 Using UK primary care data, we have previously found that people with IPF had an increased risk of acute coronary syndrome, angina and prescription of cardiovascular drugs compared to the general population, even before the diagnosis of IPF was made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 A recent study of 73 IPF and 56 COPD patients found the prevalence of coronary artery disease was higher in those with IPF (65.8% vs. 46.1%), with more severe disease also being more common in those with IPF. 5 People with IPF who have severe coronary artery disease also appear to have worse outcomes. 5 Using UK primary care data, we have previously found that people with IPF had an increased risk of acute coronary syndrome, angina and prescription of cardiovascular drugs compared to the general population, even before the diagnosis of IPF was made.…”
Section: Discussionmentioning
confidence: 99%
“…5 People with IPF who have severe coronary artery disease also appear to have worse outcomes. 5 Using UK primary care data, we have previously found that people with IPF had an increased risk of acute coronary syndrome, angina and prescription of cardiovascular drugs compared to the general population, even before the diagnosis of IPF was made. 3 We also found that the risk of acute coronary syndrome increased to three-fold in people with IPF compared to the general population after the diagnosis of IPF was established (RR 3.14, 95%CI: 2.02-4.87).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the follow up period, again there was an increased risk of acute coronary syndrome (RR, 3.14; 95% CI, 2.02 to 4.87) with the mean follow up of 2.7 years from the date of diagnosis of IPF. In a comparative study between transplant candidates for COPD and IPF, Nathan et al showed that the prevalence of CAD was found to be 65.8% in the IPF group compared to 46.1% in patients with COPD (p < 0.028) (26).…”
Section: Cardiac Arrhythmias and Ipfmentioning
confidence: 99%
“…Age, sex, ethnicity, smoking are the common predictors of mortality in IPF. Although, the most common cause of death in IPF patients is respiratory failure from progression of the disease, death due to cardiac disease have been reported in the patients (26). It has a significant impact on the mortality and hospitalizations related to IPF ( Table 1).…”
Section: Impact Of Cardiac Manifestations Of Ipfmentioning
confidence: 99%